Flouting Maxim in Spider-Man: No Way Home Movie - Sari, Putri Mayang; Jamaris, Anita (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
The aims of this research are to find out the types of Flouting Maxim and Flouting Maxim that most frequently occurred in the Spider-Man: No Way Home movie. This research used Cooperative Principles theory that proposed by Grice (1975). The researcher used descriptive qualitative method and documentation techniques in collecting data. The data of this research were taken from the utterances by all the characters in the Spider-Man: No Way Home movie. Based on the result, the researcher found 32 data contained Flouting Maxim based on Grices theory. The researcher found 4 types of Flouting Maxim, there are; 7 data of Flouting Maxim of Quantity, 8 data of Flouting Maxim of Quality, 10 data of Flouting Maxim of Relation, and 7 data of Flouting Maxim of Manner. Based on the result, it can be concluded that Flouting Maxim of Relation is the Flouting Maxim that most frequently occurred in the Spider-Man: No Way Home movie.